2021
DOI: 10.3390/su13158463
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder’s Perspective on Green Building Rating Systems in Saudi Arabia: The Case of LEED, Mostadam, and the SDGs

Abstract: This paper discusses in detail the current level of awareness of the Saudi Arabia stakeholders regarding the use and application of green building rating systems. The paper used a mix of qualitative and quantitative research methods through an exploratory method that utilized an online survey targeting experts and construction stakeholders to fill the gap of previous research papers and support the argument of the increase in the level of the awareness of stakeholders in the use and application of green buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In Saudi Arabia, the Mostadam Certification System was developed a few years ago. Furthermore, research by Al-Surf et al discussed the level of AEC stakeholders' awareness in Saudi Arabia with regard to green certification systems and the results have shown that the level of awareness has improved with respect to previous studies [156]. In addition, 57.5% of the respondents elected to use LEED, while the remaining 42.5% chose to use local recognised systems in Mostadam.…”
Section: Discussion and Resultsmentioning
confidence: 93%
“…In Saudi Arabia, the Mostadam Certification System was developed a few years ago. Furthermore, research by Al-Surf et al discussed the level of AEC stakeholders' awareness in Saudi Arabia with regard to green certification systems and the results have shown that the level of awareness has improved with respect to previous studies [156]. In addition, 57.5% of the respondents elected to use LEED, while the remaining 42.5% chose to use local recognised systems in Mostadam.…”
Section: Discussion and Resultsmentioning
confidence: 93%
“…According to data published by pertinent authorities, nearly 70% of the world's population will reside in urban settings by 2050 [30]. The rapid growth of the global urban population drives the dynamic development of cities [31]; urban areas provide a home to 10 billion trees [1], which will play an increasingly essential role in preserving livable cities in the face of population and climatic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is rational to address stakeholders’ legitimacy and power as the performance mandates in the environmental performance. Al-Surf et al (2021) mentioned that individuals must become sustainability change-makers if they are urged to engage and create sustainable buildings. The stakeholders that involve during the planning and procurement phase of the green buildings must require the capabilities in knowledge, skills and behaviour that legitimate them to contribute to sustainable development (Al-Surf et al , 2021).…”
Section: The Analysis and Discussion Of Findingsmentioning
confidence: 99%